And freedom tastes of reality: social banditry in Roman Palestine - Pirateli, Marcos Roberto (Romanitas - Revista de Estudos Grecolatinos, 2022)
Current paper discusses social banditry in Palestine during Roman times and deals with the articulation of two social categories, namely, subaltern social groups (exploited and oppressed classes), analyzed by Gramsci, and social banditry (archaic forms in social movements), analyzed by Hobsbawm. Josephus Flavius´s The Jewish War is the text under focus. Rome´s violent incursions in the region from the time of Pompey in 63 BC till the destruction of the Temple of Jerusalem in 70 AD brought about social struggles in Jewish territories, especially in Galilee, the homeland of bandits, outlaws and rebels led by false Messiahs. Banditry occurred within the non-idyllic process for the Romanization of Palestine where foreign dominators allied to the local dominant classes transformed life through the expropriation and taxation of the exploited classes, especially the peasants. Their resistance started as a struggle for survival and transformed itself in wars for Jewish freedom.
Keywords: Roman Palestine; Jewish resistance; Social banditry; Subaltern social groups; Class wars